Skrining Tekanan Darah dan Gula Darah pada Masyarakat di Desa Buki, Kabupaten Selayar, Sulawesi Selatan - Achmad Syuaib; Abdul M Ukratalo; Abdur Rahman Assagaf (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and coronary heart disease are among the leading causes of death in Indonesia. Health screening is an effective method in the prevention of NCDs, particularly for measuring blood pressure and blood glucose levels. The objective of this community service activity is to identify individuals at high risk of developing hypertension and diabetes mellitus, as well as to raise public awareness about the importance of adopting a healthy lifestyle as a preventive measure against these two diseases. This activity utilized a social health service approach, with the main focus being to provide free healthcare services to the community in Buki Village, Selayar Regency, South Sulawesi. A total of 50 participants attended this activity. The program was divided into three phases: preparation, implementation, and evaluation. The results of the community service show that, out of the 50 participants who underwent health screening, 6 individuals were found to have hypertension and 2 individuals had diabetes mellitus. This activity not only helped increase public awareness of the risks of NCDs but also served as an effective preventive step to avoid the progression of more serious health conditions in the future.